A study on historical and social background and the newness of language use in ‘Pride and Prejudice’ by Jane Austen . M.A Thesis - Nguyễn, Kim Oanh (University of Languages and International Studies, 2017)
M.A. Thesis Linguistics -- University of Languages and International Studies. Vietnam National University, Hanoi, 2012